Evaluation of Islamic Religious Education: Optimal Approach to Increase Tolerance - Fitriani, Ely; Kusaeri, Kusaeri; Hilmy, Masdar (Program Studi Pendidikan Agama Islam, 2023)
Inter-religious tolerance is one of the noble values of Islam that is important to be maintained and preserved. Efforts to increase tolerance can be made in several ways, one of which is through education. This article reviews the importance of integrating cultural values in the Islamic religious education curriculum as a strategy to reduce the potential for radicalism and increase intercultural tolerance in Indonesia. The method used in this research is a systematic literature review (SLR), using the Google Scholar and Scopus databases using the Publish or Perish 8 tool with the PRISMA technique. The search results found a total of 332 articles, then excluded 42 articles that were retained for analysis and assessed for quality and relevance according to the research questions. The results of this study show that the majority of research focuses on the Indonesian context, which sees an urgent need for tolerance education in pluralistic societies. Diverse research approaches, ranging from the development of multicultural education programs to religious text-based learning models, show the dynamics of teaching tolerance. The findings also highlight the importance of interactive and participatory learning methods and the critical role of local wisdom in tolerance education. By presenting a comprehensive literature review, this article provides valuable insights for policymakers, educational practitioners, and researchers in designing effective educational strategies to counter radicalism and strengthen intercultural tolerance through Islamic religious education.